Head-Elevated Patient Positioning Decreases Complications of Emergent Tracheal Intubation in the Ward and Intensive Care Unit. Issue 5 (October 2016) - Khandelwal, Nita; Khorsand, Sarah; Mitchell, Steven H.; Joffe, Aaron M.
Abstract : (Abstracted from Anesth Analg, 122:1101–1107, 2016) Proper patient positioning, such as using the back-up head-elevated (BUHE) position, has been reported to improve glottic views in direct laryngoscopy and prolong allowable apnea times during surgery. However, data regarding the efficacy of BUHE positioning in reducing emergency tracheal intubation (ETI)–related complications are still lacking.